Implikasi Transfer Pricing: Dampaknya bagi Praktik Corporate Tax Planning - Erma Wulan Sari; Umatun Markhumah (Universitas PGRI Madiun, 2023)
This study aims to determine the effect of Transfer Pricing on Tax Planning practices. The dependent variable used in this study is Tax Planning while the independent variable is Transfer Pricing. The population in this study are Real and Estate companies listed on the IDX for the 2018-2021 period. The sampling technique used in this study was purposive sampling so that a total sample of 48 companies was obtained with a total data of 192. The data analysis technique in this study used Simple Linear Regression Analysis with SPSS 25. Before carrying out the simple linear regression analysis test, a classical assumption test was carried out. Based on the results of the hypothesis testing, it shows that Transfer Pricing has an effect on Tax Planning Practices.